GIS mapping and survey for powdery mildew severity on linseed (Linum usitatissimum L.) in Northern Karnataka: GIS MAPPING AND SURVEY FOR POWDERY MILDEW SEVERITY ON LINSEED IN NORTHERN KARNATAKA - ARSHIYA ANJUM; D S ASWATHANARAYANA; K AJITHKUMAR; M R GOVINDAPPA; S A BIRADAR (Journal of Oilseeds Research, 2016)
Powderymildewoflinseed caused byLeveillula taurica (Lev.) Arn. is one ofthe economicallyimportant disease causing yield loss up to 60 per cent. Survey conducted in Northern Karnataka to assess the severity of linseed powdery mildew during rabi of 2014-15 revealed that mean maximum powdery mildew was observed in Raichur (98.00) followed by Bellari (32.50), Bidar (19.00), Vijayapura (17.66), Koppal (14.00), Yadgir (13.00) and least per cent disease index was observed in Kalaburgi (11.85). During the survey it was observed that the incidence of the disease was maximum in Raichur district, this may be due to the fact that crop coincides with the favourable weather factors such as cold temperature at night and warm days, no rainfall during crop growth period, continuous cultivation of linseed crop in the same area might have provided the primary source of inoculum.